Celebrating Robin Watkins' 5th Birthday at Frances Kamp's Home - Watkins, Howard::::::::: (1987)
Robin Watkins and Cheri Brosmer by cubbies at Fresno Family Day Care TV screen says "CHERI BROSMER 4 YEARS OLD"